Субъект промышленной деятельности в социально-личностном измерении - Суименко, Е. (Социология: теория, методы, маркетинг, 2001)
The author discusses which social, psychological and personal features are inherent to
employees and owners of industrial enterprises and which of them correspond to
market economy. By basing on the data of all-Ukrainian poll, the author studies ways
of formation and functioning of life principles, social and value orientations, social
well-being and expectations revealing in behavior of various subjects. As concluded, in
industrial production environment, new born social statuses and functional
requirements do not lead to the adequate behavioral reactions.